The Use of Cohesive Devices to Achieve Coherence in the Background Section of the Students' Formal Writing - Amperawaty, Anis; Warsono, Warsono (Universitas Negeri Semarang, 2019)
A good writing is one that is cohesive and coherence. Cohesive and coherence are essential textual components to create organized and comprehensiveness of the texts. Coherence refers to the quality of being meaningful or we can say that coherence is when a text hangs together. The research has been intended to find cohesion and coherence devices in the background sections of the students’ formal writing. The sources were 10 background sections of the students’ final projects from undergraduate students at Universitas Negeri Semarang. The qualitative analysis was performed to explore the results. The results of the analysis showed that the background sections of the students’ formal writing contain all kinds of cohesion and coherence devices. The background sections of the students’ final project contain grammatical cohesion (reference, ellipsis, substitution, conjunction) and lexical cohesion (reiteration and collocation). Coherence devices (theme-rhyme and micro level) are also contained in the data. Through this article the writers want to help students to have a better understanding of making background sections in their final projects.